Two new and effective food-extracted immunomodulatory agents exhibit anti-inflammatory response activity in the hACE2 acute lung injury murine model of COVID-19 - Liu, Shasha; Wang, Baiqiao; Chen, Tianran; Wang, Hui; Liu, Jinbo; Zhao, Xuan; Zhang, Yi (Frontiers in Immunology, 2024)
The coronavirus disease 2019 (COVID-19) spread rapidly and claimed millions of lives worldwide. Acute respiratory distress syndrome (ARDS) is the major cause of COVID-19-associated deaths. Due to the limitations of current drugs, developing effective therapeutic options that can be used rapidly and safely in clinics for treating severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections is necessary. This study investigated the effects of two food-extracted immunomodulatory agents, ajoene-enriched garlic extract (AGE) and cruciferous vegetables-extracted sulforaphane (SFN), on anti-inflammatory and immune responses in a SARS-CoV-2 acute lung injury mouse model. Our results showed that AGE and SFN significantly suppressed the symptoms of interstitial pneumonia, effectively inhibited the production of inflammatory cytokines, decreased the percentage of inflammatory cell populations, and elevated T cell populations in the mouse model. Furthermore, we also observed that the gut microbiome of genus Paramuribaculum were enriched in the AGE-treated group. Here, for the first time, we observed that these two novel, safe, and relatively inexpensive immunomodulatory agents exhibited the same effects on anti-inflammatory and immune responses as neutralizing monoclonal antibodies (mAbs) against interleukin 6 receptor (IL-6R), which have been suggested for treating COVID-19 patients. Our results revealed the therapeutic ability of these two immunomodulatory agents in a mouse model of SARS-CoV-2 acute lung injury by promoting anti-inflammatory and immune responses. These results suggest that AGE and SFN are promising candidates for the COVID-19 treatment.